Essentialism Versus Complexity: Conceptions of Racial Identity Construction in Educational Scholarship - Gosine, Kevin (Canadian Journal of Education/Revue canadienne de l’éducation, 2002)
In this article, I critically review North American education-related literature on identity construction among Black youth. I integrate this body of scholarship to reveal an implicit two-pronged model for examining identity among racialized persons. The first level of analysis involves unveiling collective strivings for a coherent racial identity in the face of a racist society. The second level concerns the underlying complexity, rupture, and ambivalence that such collective quests for identity tend to mask. Multicultural and antiracism education fail to adequately consider the second level of identity, resulting in both approaches presenting an oversimplified and unsatisfactory view of racial and cultural diversity. Keywords: race, ethnicity, identity, poststructuralism Dans cet article, je présente une analyse critique de la documentation scientifique nord américaine dans le domaine de l’éducation en ce qu’elle traite de la construction de l’identité chez les jeunes noirs. Je fais ressortir de ce corpus un modèle d’analyse implicite comportant deux axes. Le premier niveau d’analyse implique le dévoilement des efforts collectifs pour en arriver à une identité raciale cohérente par rapport à une société raciste. Le deuxième niveau d’analyse porte sur la complexité, la rupture et l’ambivalence sous- jacentes que ces quêtes d’identité collectives ont tendance à masquer. L’éducation multiculturelle et antiraciste ne parvient pas à considérer adéquatement le deuxième niveau d’identité, ce qui donne lieu, dans les deux approches, à une analyse simpliste et insatisfaisante de la diversité raciale et culturelle. Mots clés : race, origine ethnique, identité, poststructuralisme